2020
DOI: 10.2478/raon-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation radiotherapy for patients with extended disease small cell lung cancer in a single tertiary institution: impact of dose and perspectives in the era of immunotherapy

Abstract: BackgroundConsolidation radiotherapy (cRT) in extended disease small cell lung cancer (ED-SCLC) showed improved 2-year overall survival in patients who responded to chemotherapy (ChT) in CREST trial, however results of two meta - analysis were contradictive. Recently, immunotherapy was introduced to the treatment of ED-SCLC, making the role of cRT even more unclear. The aim of our study was to access if consolidation thoracic irradiation improves survival of ED-SCLC patients treated in a routine clinical pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In case of complete or partial response, consideration of TR is recommended, especially in patients with residual mediastinal tumors and low extra-thoracic metastatic burden. However, a survival benefit of consolidative TR after immunotherapy has been proposed [14,15] and seems worthwhile pursuing, as it would combine two treatments which have been shown to improve survival in this aggressive disease. Furthermore, the combination of radiotherapy and immunotherapy has proven both safe and beneficial regarding survival benefit in non-small cell lung cancer [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of complete or partial response, consideration of TR is recommended, especially in patients with residual mediastinal tumors and low extra-thoracic metastatic burden. However, a survival benefit of consolidative TR after immunotherapy has been proposed [14,15] and seems worthwhile pursuing, as it would combine two treatments which have been shown to improve survival in this aggressive disease. Furthermore, the combination of radiotherapy and immunotherapy has proven both safe and beneficial regarding survival benefit in non-small cell lung cancer [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…However, a survival benefit of consolidative TR after immunotherapy has been proposed [ 14 , 15 ] and seems worthwhile pursuing, as it would combine two treatments which have been shown to improve survival in this aggressive disease. Furthermore, the combination of radiotherapy and immunotherapy has proven both safe and beneficial regarding survival benefit in non-small cell lung cancer [ 16 19 ].…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 The application of consolidation radiotherapy in selected patients with extensive-stage disease (ED) and a good initial response to chemotherapy have partly contributed to the improved survival rate, but application has been very inconsistent. 12 , 13 Immunotherapy has resulted in significant progress in the treatment of numerous malignant diseases, including non-small cell lung cancer (NSCLC). Expectations for the treatment of small cell lung cancer were high as well.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, early RT especially within 6 cycles of chemotherapy prolong local recurrence-free survival (p = 0.001) and hyper-fractioned scheme (45 Gy in 30 fractions twice per day) has survival advantage over 60 Gy/30 fractions daily, which in line with Luan's finding [25]. However, Stanic et al concluded that higher dose resulted in better OS [26]. In our study, subgroup analysis showed no discrepancy of PFS and OS between BED > 60 Gy and < 60 Gy.…”
Section: Discussionmentioning
confidence: 67%